Mutations in chikungunya virus nsP4 decrease viral fitness and sensitivity to the broad-spectrum antiviral 4'-Fluorouridine. - Peiqi Yin; Elizabeth B Sobolik; Nicholas A May; Sainan Wang; Atef Fayed; Dariia Vyshenska; Adam M Drobish; M Guston Parks; Laura Sandra Lello; Andres Merits; Thomas E Morrison; Alexander L Greninger; et al. (PLoS Pathogens)
Chikungunya virus (CHIKV) is an arthritogenic alphavirus that has re-emerged to cause large outbreaks of human infections worldwide. There are currently no approved antivirals for treatment of CHIKV infection. Recently, we reported that the ribonucleoside analog 4'-fluorouridine (4'-FlU) is a highly potent inhibitor of CHIKV replication, and targets the viral nsP4 RNA dependent RNA polymerase. In mouse models, oral therapy with 4'-FlU diminished viral tissue burdens and virus-induced disease signs. To provide critical evidence for the potential of 4'-FlU as a CHIKV antiviral, here we selected for CHIKV variants with decreased 4'-FlU sensitivity, identifying two pairs of mutations in nsP2 and nsP4. The nsP4 mutations Q192L and C483Y were predominantly responsible for reduced sensitivity. These variants were still inhibited by higher concentrations of 4'-FlU, and the mutations did not change nsP4 fidelity or provide a virus fitness advantage in vitro or in vivo. Pathogenesis studies in mice showed that the nsP4-C483Y variant caused similar disease and viral tissue burden as WT CHIKV, while the nsP4-Q192L variant was strongly attenuated. Together these results support the potential of 4'-FlU to be an important antiviral against CHIKV.